Janus kinase inhibitors in systemic lupus erythematosus: implications for tyrosine kinase 2 inhibition - Dionysis Nikolopoulos; Dionysis Nikolopoulos; Ioannis Parodis; Ioannis Parodis; Ioannis Parodis (Frontiers in Medicine, 2023)
Aberrant activation of the Janus kinase (JAK) and signal transducer and activator of transcription (STAT) pathway is common in systemic lupus erythematosus (SLE), conferring immune-mediated properties in target tissues. Multiple cytokines activate different combinations of JAKs and STATs to alter the cell fate of target tissue and induce end-organ damage. Thus, the simultaneous blockade of several different cytokines by small molecules acting downstream intracellular signalling has gained traction. JAK inhibitors have been approved for the treatment of several rheumatic diseases, yet hitherto not for SLE. Nevertheless, JAK inhibitors including tofacitinib, baricitinib, and deucravacitinib have shown merit as treatments for SLE. Tofacitinib, a JAK1/3 inhibitor, reduced cholesterol levels, improved vascular function, and decreased the type I interferon signature in SLE patients. Baricitinib, a JAK1/2 inhibitor, demonstrated significant improvements in lupus rashes and arthritis in a phase 2 and a phase 3 randomised controlled trial, but the results were not replicated in another phase 3 trial. Deucravacitinib, a selective tyrosine kinase 2 (TYK2) inhibitor, yielded greater response rates than placebo in a phase 2 trial of SLE and will be investigated in larger phase 3 trials. TYK2 is activated in response to cytokines actively involved in lupus pathogenesis; this review highlights the potential of targeting TYK2 as a promising therapy for SLE.